مستوى ترمجة معاين الكلمات العربية لدى طلبة الشهادة العالية الدينية املاليزية (STAM )مبدرسة تونكو أمفوان رحيمة الدينية اإلسالمية العالية - Izzah Syakirah binti Maaruf
The number of STAM holders with an excellent score increased each year, but the candidate of Malaysian students who are failed on the entrance exam at Al-Azhar University also increased. The aims of this research are to determine the level of translation of Arabic words meanings among form six students at the Tengku Ampuan Rahimah Islamic High School (SAMTTAR), and to analyze the relationship between their trial examination and their level of translation. In this research, the researcher uses the descriptive method (ie, description, percentage and correlation). The researcher randomly selects 80 form six students at SAMTTAR and using the test, which requires 66 words to be translated. Those words are taken from the textbooks. The expected results of the research showed that the level of translation of nouns and verbs are at the lowest level. While, the correlation coefficient score indicates the intermediate level relationship between the trial examination of STAM and the results of the Arabic words translation in this paper. The research recommends that translation training in the classroom and extra-curricular activities are important in the process of learning Arabic language.